IMPACT OF FLOODING ON HOUSING QUALITY AND LIVABILITY IN RIVERINE COMMUNITIES OF KEBBI STATE, NIGERIA: A REVIEW FOR SUSTAINABLE STRATEGIES - Kwaifa, Mustafa Muhammad; Sanni, Lekan Mohammed; Akande, Olaide Sheerifdeen; Adeleye, Bamiji Micheal (FUDMA Journal of Sciences, 2026)
This study examines the impacts of flooding on residential infrastructure and community well-being in riverine settlements. Armchair analysis and review of recent literature were used to extract relevant information for the study. The review identifies four key impact dimensions: structural damage and material degradation, indoor environmental quality deterioration, socio-economic implications, and community resilience challenges. Findings demonstrate that flooding leads to structural damages and drastic decrease of property value of the degraded structures, compromised indoor air quality with mold spore concentrations 200-40%. The study also highlights critical gaps in insurance coverage affecting 70% of 500% above baseline, households and substantial socio-economic burdens, particularly on vulnerable populations. Additionally, the study explores the socioeconomic implications of flood-related housing damage, including property devaluation, increased maintenance costs, and insurance challenges. The paper concludes by proposing evidence-based recommendations for flood-resilient housing design, policy interventions, and community-level adaptation strategies to enhance housing sustainability in flood-prone areas. This comprehensive analysis contributes to the growing body of knowledge on climate change adaptation and sustainable urban development in vulnerable riverine settlements. Key recommendations for enhancing community resilience were advanced, including implementing flood-resistant construction strategies, updating building codes, developing comprehensive emergency response networks, and establishing financial assistance programs.